1976
DOI: 10.2135/cropsci1976.0011183x001600040007x
|View full text |Cite
|
Sign up to set email alerts
|

Periods of Chilling Sensitivity in Germinating Pima Cottonseed1

Abstract: Seed germination and seedling development are adversely affected in many crops by less than lethal chilling temperatures. Periods of chilling sensitivity have been identified in Upland cotton (Gossypium hirsutum L.) but little work has been reported in Pima cotton (G. barbadense L.). This study was conducted to evaluate the influence of temperature on the degree and timing of chilling susceptibility in germinating Pima cotton and to determine if genetic variability exists. Seed were germinated at 25 or 35 C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…have noted that a different sort of chilling injury can be observed following cold treatment after about 2 days of imbibition (3,4). Our data in Figure 2 similarly suggest that in addition to the damage during initial water entry, some damage occurs from chilling at later times.…”
Section: Discussionsupporting
confidence: 62%
“…have noted that a different sort of chilling injury can be observed following cold treatment after about 2 days of imbibition (3,4). Our data in Figure 2 similarly suggest that in addition to the damage during initial water entry, some damage occurs from chilling at later times.…”
Section: Discussionsupporting
confidence: 62%
“…Cole and Christiansen (1975) observed reduced per cent germination of Pima S-4' (G. barbademe L.) than genetic selection M-8 (Gossypium hirsutum L.) over same temperature range after seeds were subjected to different durations of chilling time. Buxton et al (1976) observed similar responses of commercial pima type cultivars to chilling at 5°C, but significant differences at 7 and 10°C and concluded that higher temperatures (>5°C) are more desirable for selection of cold-tolerant genotypes in cotton. Likewise, Christiansen (1968) observed that genotypes of G. hirsutum, L. M-8 and Deltapine 14, showed a similar response to exposure of chilling temperatures during initial hours of imbibition.…”
mentioning
confidence: 85%
“…Buxton et al. () observed similar responses of commercial pima type cultivars to chilling at 5°C, but significant differences at 7 and 10°C and concluded that higher temperatures (>5°C) are more desirable for selection of cold‐tolerant genotypes in cotton. Likewise, Christiansen () observed that genotypes of G. hirsutum , L. M‐8 and Deltapine 14, showed a similar response to exposure of chilling temperatures during initial hours of imbibition.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Once imbibition begins, seeds pass through one or 2 periods of increased sensitivity to chilling injury, depending upon the species (14). The first period coincides with the onset of im bibition and has been observed in many crop seeds (3,10,13), including chickpeas (Table 2). For chickpea seeds, the period most sensitive to chilling injury was the first 30 min of imbi bition.…”
Section: Discussionmentioning
confidence: 79%